Signage and wayfinding design a complete guide to creating environmental graphic design systems - Calori, Chris (John Wiley & Sons, Inc., 2015)
"Covers development of room/space numbering systems, approaches to sign typing and numbering, and message schedule management"-- Provided by publisher.